PENYULUHAN TENTANG DAUN KENIKIR TERHADAP PENYEMBUHAN LUKA DI PUSKEMAS PANCUR BATU - Wahyudi Wahyudi; Dewi Safitri Ginting (Jurnal Pengabdian Masyarakat Putri Hijau, 2021)
Government assistance Improvement by Government assistance Center Gatherings Means To Additional Foster Government assistance Degrees To The Most elevated Level. A work to pass on data identified with the field likewise laborers to the local area and their relatives either straightforwardly or in a roundabout way. General wellbeing training is an action or movement. endeavors to pass on wellbeing messages to people in general, gatherings or people. With the expectation that with this impression or people can acquire information about better wellbeing. At last, this information is relied upon to influence their conduct. to change target conduct. To accomplish this objective, a proactive and dynamic organization and procedure is required that covers all fields, both government, private and local area, particularly in the treatment of wounds or wounds even an irritation. One way that should be possible to fabricate the worth of government assistance is the neighborhood level, in this way directing is completed on normal medications, particularly establishes that can be utilized as treatment choices, particularly kenikir leaves which have different sorts of gainful substances and have demonstrated viability. Kenikir leaves contain a few substances that have many advantages both as lab tests and for wellbeing which show that Kenikir leaves are rich in ascorbic corrosive and chlorogenic corrosive, being bountiful in cell fortifications, flavonoid compounds, starches, proteins, minerals, supplements and phenolic compounds . Kenikir leaves are additionally one of the plants that have the most noteworthy quercetin content of 10 Indonesian plants, specifically 51.28 Mg/100 Mg (Cheng, et al, 2015). Quercetin is an assortment of flavonoid promoters that have benefits as alleviating, malignancy counteraction specialists, cytoprotective, neuroprotective, vasoprotective and have proliferative impacts at a high cell level.